(untitled) (Web of Teachers: Inderscience Research, 2025)
This paper explores the role of speech etiquette in communication, emphasizing its importance in fostering effective and respectful interactions across various cultural and professional contexts. Speech etiquette, encompassing both verbal and non-verbal elements, is essential in ensuring clarity, reducing misunderstandings, and building positive relationships between individuals. The study reviews existing literature, presents findings from case studies, and analyzes data collected from surveys and interviews to examine the impact of speech etiquette in diverse communication settings. The results highlight the significant role of speech etiquette in relationship building, the variations across cultures, and its influence on professional and social dynamics. The discussion underscores the importance of cultural sensitivity and the evolving nature of etiquette in the digital age. Ultimately, the paper concludes that speech etiquette remains a fundamental aspect of communication, essential for promoting intercultural dialogue, professionalism, and mutual respect in both personal and professional environments.